A test of the efficiency of the aluminium and copper markets at the London Metal Exchange - Martin Gross (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
In a futures market hedgers can secure a certain price for a commodity at a future delivery date. The futures price also conveys information about the cash price at the maturity of the futures contract in that it reflects the different cash price expectations of the market participants at the time of contracting. Such information will be particularly important for agents not fully hedged as well as for market participants planning for future production or use. This paper will concentrate on information aspects of futures prices and will disregard the security trade aspect.
Keywords: 330